Pigiasilluta oKalagiamik: Culturally Relevant Assessment in Nunatsiavut - Godfrey Anderson, Jennifer; Lane, Jodie (Études Inuit Studies, 2020)
Beginning with a story of travelling between northern communities and the shared experiences of the researchers, the environment, and the animals, this research reports the perspectives of teachers, administrators, and parents on how school-based assessment practices impact Inuit learners in Nunatsiavut, the Labrador Inuit Settlement Area. To adjust to current global social, economic, and environmental challenges (Council of Ministers of Education 2018; OECD 2018; United Nations 2010), mainstream jurisdictions are centering their curricular content and assessment measures on competencies (Alberta 2018; British Columbia 2018; Council of Ministers of Education 2018; OECD 2018; Ontario 2016). Our results show that many of these values are already imbedded in community- and land-based experiences in Nunatsiavut and we argue that the development of assessment practices to capture competencies can help reveal the strengths in culturally relevant curriculum and instruction in Nunatsiavut.